Straßenbau im Mahel von Mali (Gourma) als Entwicklungsinstrument. Wirtschaftsräumliche Konsequenzen für traditionelle Überlebensökonomien - Wagner, Horst-Günter (ERDKUNDE, 1988)
The Republic of Mali's regional policy seeks to reduce econo-spatial disparities between central and peripheral provinces. Helping to realize this aim a bituminized all year road from Mopti/Sevare to Gao (ca. 600 km) was constructed and finished in 1986. The following contri bution tries to demonstrate first positive and negative effects of this new road. The observations are based on field studies undertaken under the aegis of the German Ministry of Economic Cooperation in December 1986. Within the transport sector an increase in the volume of traffic can be observed. Simultaneously the transport tariffs were raised by 100% by the administration, however. The central place markets of the semi-arid Gourma region are now reached by food and non-food goods from the southern and the more humid parts of the country. Besides this imported industrial products are intruding into the traditional market-spectrum. Regional price disparities of cereals are now diminishing. As was to be expected, effects upon crafts and small industries are still unimportant. By comparison with these branches agriculture shows remarkable changes. Negative effects are indicated by the extension of millet-cultivation into former pasture regions with high rainfall variability in the case of setlement of former nomads near the road: desertification is increasing here. The effects of the new road on stock-farming are also ambiguous: rising cash-income in favour of nomads contrasts with the increase in overgrazing, which is pushing forward the destruction of vegetation, soil erosion and desertification. Generally speaking it is to be expected that the negative effects of the new road upon the ecological system operate more quickly than the positive results of stabilizing and improving the traditional economy.